Portrait of a body - Delporte, Julie (Drawn & Quarterly, 2024)
"As she examines her life experience and traumas with great care, Delporte faces the questions about gender and sexuality that both haunt and entice her. Deeply informed by her personal relationships as much as queer art and theory, Portrait of a Body is both a joyous and at times hard meditation on embodiment--a journey to be reunited with the self in an attempt to heal pain and live more authentically. Delporte's idyllic colored pencil drawings contrast with the near urgency that structures her confessional memoir. Each page is laden with revelation and enveloped in organic, natural shapes--rocks, flowers, intertwined bodies, women's hair blowing in the wind--captured with devotion. The vitality of these forms interspersed with Delporte's flowing handwriting hold space for her vivid and affecting observations. Skillfully translated by Helge Dascher and Karen Houle, Portrait of a Body provokes us to remain open to the lessons our bodies have on offer."--Amazon.com.